Enhancing Consumer Online Purchase Intention Through Gamification in China: Perspective of Cognitive Evaluation Theory - Xu, Yan; Chen, Zhong; Peng, Michael Yao-Ping; Anser, Muhammad Khalid (Frontiers in Psychology, 2020)
The application of game elements of gamification in online shopping is attracting interest from researchers and practitioners. However, it remains unclear how gamification affects and improves consumer purchase intention on online shopping platforms, which still leaves a gap in our knowledge. To narrow this theoretical gap, a theoretical model has been built in this study. This model adopts cognitive evaluation theory to explain the impact of gamification elements on consumer purchase intention. Data was collected from 322 online shopping consumers who used a flash game to test their purchase intention after playing games. The results show that game rewards, absorption and autonomy of gamification positively enhance sense of enjoyment, and that it helps people meet their psychological needs, which ultimately affects the online purchase intention of consumers. This study is helpful in analyzing the factors involved in the successful introduction of gamification on online shopping platforms in more detail.